Variación de la liquidez durante la pandemia por COVID-19 en empresas de Iberoamérica: Una revisión de la literatura - Johana Consuelo Carrera Villarreal; Nayleha Dina Hinostroza Aldas; Carlos Alberto Vásquez Villanueva (My University, 2023)
A company with insufficient liquidity will face serious challenges. The COVID-19 pandemic altered the financial landscape and challenged business management; therefore, this study aimed to describe the liquidity of Ibero-America companies during this health crisis through a literature review. The research was a bibliographic review. Fourteen scientific studies conducted between 2020 and 2022 were selected and analyzed using documentary analysis. The study of liquidity indices revealed that Ibero-American companies were adversely affected by the health emergency—even those with a positive economic balance—which jeopardized their working capital to meet financial obligations and rendered accounts receivable uncollectible.
Keywords: Accounts receivable; Market liquidity; Business; Liquidity crisis; Pandemic; Capital (architecture); Face (sociological concept); Financial analysis; Scientific literature; Welfare economics; Political science; Working capital; Coronavirus disease 2019 (COVID-19); Revenue; Economy; Economics; Finance; Work (physics); Accounting; Financial plan; Financial crisis; Liquidity risk; Economic impact analysis; Financial Audit; Order (exchange); Accounts receivable; Market liquidity; Liquidity crisis; Pandemic; Capital (architecture); Face (sociological concept); Financial analysis; Scientific literature; Social Sciences Business, Management and Accounting Accounting Business, Education, Mathematics Research